Centenary of the birth of the famous Ukrainian researcher of radiometeors prof. B.L. Kashcheyev (1920-2004), his heritage and trajectory measurements today - Kolomiyets, S V.v; Kolomiyets, K. A.; Kyrychenko, I. Yu.; Pryimachov, Yu. D. (Одеські астрономічні публікації, 2020)
The development of meteor radar research was stimulated during World War II by air defense requests to rule out false alarms of radars on meteoroid intrusions. After the war, many air defense radars were involved in scientific observations of meteors. An additional stimulus for interest in the study of radiometeors was the phenomenon of the Draconid meteor shower in 1946, which was recorded by the radio method as extraordinary. We can talk about the scientific and technological revolution of this period, associated with the use and boom in the development of radio technology and missile technology. The ballistics of the movement of airborne objects in the Earth’s atmosphere (and outside the atmosphere since 1957) of artificial and natural origin is becoming increasingly complex. Radio technology could not have developed without knowledge of the ionosphere and the effects of the Sun on radio communications, along with the effects of the Sun on the ionosphere. In the ionosphere, a layer at altitudes of 70-130 km is called the meteor zone, i.e. the zone where cosmic bodies, burning in the Earth’s atmosphere, cause the appearance of ionized meteor tracks, which interact with radar radiation and reflect it. This allows the radar receiver to record the reflected signal. In the presence of three receivers spaced 3-5 km apart (and located approximately at the vertices of a right triangle), it is possible to determine the guiding cosines of the trajectory of the meteoroid in the Earth’s atmosphere. Continuing the trajectory of the meteoroid to the intersection with the celestial sphere at infinity, we obtain a point called the meteor radiant. In basic optical meteor observations, the trajectory is determined differently than in the radio method. The article highlights the significance of the event of the centenary of the birth of the famous Ukrainian researcher of radiometeors Prof.KashcheyevB.L. ˙ (1920-2004) anditslegacy, aswell as the problems and solutions of trajectory measurements today.